Recuperação de uma área degrada por mineração no município Pindamonhangaba - VIEIRA, Felipe de Campos Almeida Antunes (2019)
Mineral exploration, despite being considered an activity that causes large environmental impact, is practiced by humans for a long time because of its great socioeconomic importance. The recovery project given area degraded by mining, can be defined as the set of actions necessary to mitigate the impacts occurring in the area, in order to compensate the loss incurred and make the area suitable for productive use in a balanced environment.This work shows the recovery of an area degraded by mining, and process parameters for a favorable cost-benefit, that meets the needs of man and minimize environmental impacts.By right of recovery area is possible to obtain favorable results that make compensatory extraction activity, thus meeting the needs of environmental and socioeconomic factors.